2012
DOI: 10.1002/bdrc.21013
|View full text |Cite
|
Sign up to set email alerts
|

Computational models for mechanics of morphogenesis

Abstract: In the developing embryo, tissues differentiate, deform, and move in an orchestrated manner to generate various biological shapes driven by the complex interplay between genetic, epigenetic, and environmental factors. Mechanics plays a key role in regulating and controlling morphogenesis, and quantitative models help us understand how various mechanical forces combine to shape the embryo. Models allow for the quantitative, unbiased testing of physical mechanisms, and when used appropriately, can motivate new e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 175 publications
(276 reference statements)
0
73
0
1
Order By: Relevance
“…Additional work using sophisticated cogels of Matrigel and other synthetic or naturally derived matrices, with tunable mechanical properties (41), will be necessary to more fully elucidate the mechanoregulatory mechanisms at work during epithelial morphogenesis. Ultimately, these problems will demand interdisciplinary collaborations between engineers, physicists, materials scientists, and cell and developmental biologists and will require new experimental (42) and computational (43) approaches to quantify the mechanical forces and material properties that shape developing tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Additional work using sophisticated cogels of Matrigel and other synthetic or naturally derived matrices, with tunable mechanical properties (41), will be necessary to more fully elucidate the mechanoregulatory mechanisms at work during epithelial morphogenesis. Ultimately, these problems will demand interdisciplinary collaborations between engineers, physicists, materials scientists, and cell and developmental biologists and will require new experimental (42) and computational (43) approaches to quantify the mechanical forces and material properties that shape developing tissues.…”
Section: Discussionmentioning
confidence: 99%
“…But researchers are increasingly realizing that many developmental processes can only be studied through multi-scale modeling (Brodland et al, 1994, Davidson 2012Wyczalkowski et al, 2012). In the following we examine in further detail how mechanical force production and propagation of stress and strain contribute to the shaping of the early embryo.…”
Section: Tissue Mechanics In Embryo Developmentmentioning
confidence: 99%
“…In the latter case, individual genes or regulatory circuits can sometimes be 'knocked out' to study their effects, but it is typically not possible to knock out a physical force. However, new experimental techniques afford an examination of physical difference making in biology (Wyczalkowski et al, 2012;Love, forthcoming). Imaging tools such as video or traction force microscopy, confocal time-lapse microscopy, and fluorescent techniques now allow for quantitative measurement of geometry changes and gradient velocities of moving cells (Brodland et al, 2010;Davidson, 2012).…”
Section: The Explanatory Power Of Macroscale Biomechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations have shown that tissue-level events, which determine the post-gastrulation body plan by executing a series of millimetersized morphogenetic deformations, are prominent in warmblooded animals. [1][2][3] Here we explore the question-To what extent, if any, are morphogenetic movements spatially regionalized at the tissue level of organization in bird embryos?…”
Section: Introductionmentioning
confidence: 99%